Jadranska orijentacija u evropskoj orijentaciji Jugoslavije - Sbutega, Antun (Promet - Traffic&Transportation, 2012)
The author deals with the economic, cultural and political aspects of the Adriatic orientation to subsequently dedicate most space to the review of traffic as an element of this every important orientation. In the closing lines the author draws references to the relationship of the Adriatic and the European orientation and pleads for better linkage of the ports with the mainland.